Evaluation of Some Physical Properties of Locally Prepared Alpha-calcium Sulfate Hemihydrate - Lamia T Rejab (University of Mosul, College of Dentistry, 2013)
Aims: Aim of the study is to evaluate some physical properties of locally prepared dental stone form natural gypsum by two different calcination methods with autoclave with and without adding crystal habit modifier during calcination procedure for different periods of time. Materials and methods: The values of some physical properties that include specific gravity, water/ powder ratio and linear setting expansion of the prepared dental stone with autoclave with and without adding crystal habit modifier during calcination procedure for different periods of time and compared with that of commercial den-tal stone. ANOVA and Duncan's multiple range test were performed to determine the significant differ-ence among the tested groups at p ≤ 0.05%. Results: Results showed that there were significant differ-ences of the values of the physical properties between the locally prepared dental stone with autoclave and the commercial one at p≤ 0.05 in specific gravity, water/ powder ratio and linear setting expansion. Conclusions :The results appeared the alpha- calcium sulfate hemihydrates dental stone that prepared in autoclave with adding crystal habit modifier has superior properties than of that prepared without modifier, but still not reach the properties of the commercial product. All values of the tested proper-ties were in accordance with ADA Specification